Haematologic malignancies with unfavourable gene mutations benefit from donor lymphocyte infusion with/without decitabine for prophylaxis of relapse after allogeneic HSCT: A pilot study. (1st May 2021) - Zhang, Rui; Wang, Lili; Chen, Peng; Gao, Xiaoning; Wang, Shuhong; Li, Fei; Dou, Liping; Gao, Chunji; Li, Yan; Liu, Daihong
Abstract: Relapse is the main cause of treatment failure for leukaemia patients with unfavourable gene mutations who receive allogeneic haematopoietic stem cell transplantation (allo‐HSCT). There is no consensus on the indication of donor lymphocyte infusion (DLI) for prophylaxis of relapse after allo‐HSCT. To evaluate the tolerance and efficacy of prophylactic DLI in patients with unfavourable gene mutations such as FLT3‐ITD, TP53, ASXL1, DNMT3A or TET2, we performed a prospective, single‐arm study. Prophylactic use of decitabine followed by DLI was planned in patients with TP53 or epigenetic modifier gene mutations. The prophylaxis was planned in 46 recipients: it was administered in 28 patients and it was not administered in 18 patients due to contraindications. No DLI‐associated pancytopenia was observed. The cumulative incidences of grade II–IV and III–IV acute graft‐versus‐host disease (GVHD) at 100 days post‐DLI were 25.8% and 11.0%, respectively. The rates of chronic GVHD, non‐relapse mortality and relapse at 3 years post‐DLI were 21.6%, 25.0% and 26.1%, respectively. The 3‐year relapse‐free survival and overall survival (OS) rates were 48.9% and 48.2%, respectively. Acute GVHD (HR: 2.30, p = 0.016) and relapse (HR: 2.46, p = 0.003) after DLI were independently associated with inferior OS. Data in the current study showed the feasibility of prophylactic DLI with/without decitabine in the early stage after allo‐HSCT in patients with unfavourable gene mutations. Abstract : This prospective, single‐arm, pilot study investigated the efficacy and feasibility of prophylactic DLI and showed that prophylactic DLI could effectively prevent relapse without increasing the incidence of GVHD or NRM for patients with unfavourable gene mutations after allo‐HSCT. In addition, prophylactic decitabine followed by DLI showed potential safety and efficacy without impact on hematologic reconstitution and with acceptable incidence of DLI‐related aGVHD.